The Influence of Liabilities and Equity on Profitability in Islamic Banks Listed on the Indonesia Stock Exchange 2021-2023 - Fazria, Rizka; Rahman, Febriani Nur; Septika, Edya Nashwa; Kania, Sherly Indah; Chrisna, Heriyati (Lembaga Riset Mutiara Akbar, 2024)
This study examines the impact of capital components in the form of liabilities and equity on the ability to generate profits in Islamic-based banks listed on the IDX for the 2021-2023 period. The results of secondary data processing using multiple regression techniques indicate a significant opposite correlation between liabilities and profitability, indicated by a coefficient value of -0.087 at a significance level of 0.000 (below 0.05). On the other hand, equity shows a meaningful unidirectional relationship with profitability, reflected by a coefficient of 1.423 at a significance level of 0.000 (below 0.05). Overall testing through the F test shows that both independent variables have a significant simultaneous effect, evidenced by the calculated F value of 26.129 at a significance of 0.000 (below 0.05). The reliability of the analysis model was confirmed through the fulfillment of all prerequisite tests including normal distribution, free of multicollinearity, heteroscedasticity, and autocorrelation symptoms. The research conclusion underlines the urgency of balancing the capital structure, with recommendations to strengthen the equity side rather than adding liabilities to encourage the improvement of Islamic banks' financial performance.